2013
DOI: 10.1038/srep02781
|View full text |Cite
|
Sign up to set email alerts
|

α-Helical Structures Drive Early Stages of Self-Assembly of Amyloidogenic Amyloid Polypeptide Aggregate Formation in Membranes

Abstract: The human islet amyloid polypeptide (hIAPP) is the primary component in the toxic islet amyloid deposits in type-2 diabetes. hIAPP self-assembles to aggregates that permeabilize membranes and constitutes amyloid plaques. Uncovering the mechanisms of amyloid self-assembly is the key to understanding amyloid toxicity and treatment. Although structurally similar, hIAPP's rat counterpart, the rat islet amyloid polypeptide (rIAPP), is non-toxic. It has been a puzzle why these peptides behave so differently. We comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 89 publications
(107 reference statements)
13
89
0
Order By: Relevance
“…68 Despite the dominant role of the cross-β-sheet in mature fibrils, 911 compelling evidence points to an intermediate role for the α-helix in the cascade. 1215 Many aggregating proteins exhibit α-helical character when associated with membrane. 1517 However, the crowded environment in cells makes the study of in vivo aggregation challenging.…”
Section: Introductionmentioning
confidence: 99%
“…68 Despite the dominant role of the cross-β-sheet in mature fibrils, 911 compelling evidence points to an intermediate role for the α-helix in the cascade. 1215 Many aggregating proteins exhibit α-helical character when associated with membrane. 1517 However, the crowded environment in cells makes the study of in vivo aggregation challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In-between perturbations include hIAPP surface adsorption and formation of channels [78][79][80][81]. Nevertheless, the single, main mechanism that makes hIAPP cytotoxic is far from being established [78]. Brender [79] has proposed two main theories of membrane disruption by hIAPP.…”
Section: Cytotoxicity Of Hiapp and Membrane Channelsmentioning
confidence: 98%
“…The effects on membranes may range from a change in fluidity and permeability to bilayer disruption and extraction of membrane lipids. In-between perturbations include hIAPP surface adsorption and formation of channels [78][79][80][81]. Nevertheless, the single, main mechanism that makes hIAPP cytotoxic is far from being established [78].…”
Section: Cytotoxicity Of Hiapp and Membrane Channelsmentioning
confidence: 99%
“…The GROMOS 53A6 force field [35,36] was used. This forcefield has been shown to perform well in simulating proteineprotein and membrane-protein systems [37,16]. The SPC (simple point charge) water model [38] was used.…”
Section: Simulation Setupmentioning
confidence: 99%
“…In particular resveratrol (trans-3,5,4 0 -trihydroxystilben), has evidenced significant beneficial effects in patients with T2DM [20]. Moreover, several studies have demonstrated that resveratrol may inhibit IAPP amyloid aggregation in the presence of negatively charged membranes [16,21]. Molecular Dynamics simulations have also demonstrated that resveratrol inhibits the aggregation of IAPP segment 22e27 by interfering with the intersheet side-chain stacking driven by aromatic rings [22] Nevertheless, there is still need of a more detailed structural characterization of the dynamics of membrane/peptide assemblies to fully understand the mechanism by which resveratrol inhibits IAPP fibrillogenesis and toxicity.…”
Section: Introductionmentioning
confidence: 97%